TRANSPLANTASI KARANG DITUBIR PADA AREA PATAHAN KARANG (RUBBLE) BEKAS PENGEBOMAN IKAN DI DESA SAWAPUDO - Almuqni, Bobby Akhyan; Setiawan, Haris; Tamsil, La Ode (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
This study to determine the success of transplantation techniques are directly applied to the area of rubble, the former fish bombing, to manipulate the substrate is unstable / shaky so it can be used as a medium for transplantation. Research is planned to last for 5 months. The research is based on completely randomized design with water depths as treatment. On nets placed at a depth of 3 meters in length t get the initial seed coral as follows: 73.2 mm, 54.6 mm, 103 mm, 74.5 mm, 83.7 mm, 110.4 mm, 51.2 mm, 67.8 mm 98.5 mm. t the beginning of this term would represent, a basic reference specimens to determine the growth rate of coral transplants.Â Keywords : Transplantation, Rubble, net scrap, Used Bombing